Do commercial forest plantations reduce pressure on natural forests? evidence from forest policy reforms in Uganda - Ainembabazi, John H.; Angelsen, A. (Elsevier, 2014)
This paper investigates if and howthe establishment of private commercial forest plantations in degraded forestreserves can conserve natural forests in Uganda. It uses difference-in-difference and decomposition analyses onhousehold data collected from intervention and control villages in the neighborhood of forest reserves. We findthat commercial forest plantations are weakly effective in conserving natural forests. The reduction in forest useis unevenly distributed across households depending on location and resource endowments such as farmlandand livestock. The results suggest that the conservation effectiveness can be enhanced by complementary interventionsthat change characteristics that reduce forest use, such as more education for forest users.